2019
DOI: 10.3389/feart.2019.00249
|View full text |Cite
|
Sign up to set email alerts
|

Time Variation in the Chemical and Isotopic Composition of Fumarolic Gasses at Kusatsu-Shirane Volcano, Japan

Abstract: Minor seismicity may occur at volcanoes with hydrothermal system before a steam eruption. To forecast any steam eruption, it is indispensable to detect and understand the nature of this shallow seismicity. As the fumarolic gas resides in the hydrothermal system, it may provide insights for elucidating the nature of any seismicity and thus forecast steam eruptions. At Kusatsu-Shirane volcano Japan, intense seismic activity took place in 2014 and 2018. To investigate the relationship between the seismicity and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…The hydrothermal system of the Kusatsu-Shirane volcano has been intensively studied by performing geochemical analysis at the Yugama crater lake and the surrounding fumaroles and hot springs (Sano et al 1994;Ohba et al 2019). Ohba et al (2019) showed a model of a two-phase gas-liquid reservoir underlain by a magmatic fluid reservoir based on the isotope ration of hydrogen and oxygen in relation to recent volcanic unrest.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrothermal system of the Kusatsu-Shirane volcano has been intensively studied by performing geochemical analysis at the Yugama crater lake and the surrounding fumaroles and hot springs (Sano et al 1994;Ohba et al 2019). Ohba et al (2019) showed a model of a two-phase gas-liquid reservoir underlain by a magmatic fluid reservoir based on the isotope ration of hydrogen and oxygen in relation to recent volcanic unrest.…”
Section: Introductionmentioning
confidence: 99%
“…The latest eruption of the SPCG occurred at YCL in 1982-1983. Recently, microearthquake swarms accompanied by ground deformation and changes in the chemistry of YCL and nearby fumaroles were detected in 1991-1992(Ohba et al 2008, 2019b.…”
Section: Kusatsu-shirane Volcano and The 2018 Eruptionmentioning
confidence: 99%
“…From March to 2016, the SPCG experienced a microearthquake swarm, ground deformation indicating an increase in volume of 1.2 × 10 5 m 3 over 20 months (Fig. S2), an increase in the Cl and SO4 concentration of YCL, and an increase in the CO2/H2S ratio of nearby fumaroles (SPCG unrest in 2014) (Ohba et al 2019b). Moreover, three months after the 2018 MPCG eruption, a shallow inflation and a marked increase in seismicity occurred at SPCG from April 2018 (MPCG-SPCG unrest in 2018).…”
Section: Relationship Between the Mpcg And Spcgmentioning
confidence: 99%
“…As expected, earthquake swarms reoccurred around the Yugama crater from March 2014 and in April 2018. Ohba et al (2019b) estimated that the earthquake swarms in 2014 and 2018 were triggered by the increased pressure in the hydrothermal reservoir due to the injection of magmatic gas, a model based on the analytical results of the chemical and stable isotopic compositions of the fumarolic gases near the Yugama crater. This result made us expect that magma-hydrothermal interaction can be inferred through the chemical composition of Yugama Crater Lake because magmatic gas contains many watersoluble components.…”
Section: Introductionmentioning
confidence: 99%